AIDS, PROFESI KEDOKTERAN, DAN KESEHATAN PUBLIK - Mubasyir Hasanbasri (Populasi, 1995)
The need for promoting individual responsibility in health is crucial particularly in the context of limited resources. In looking at a continuing increase in the number of HIV cases reported in Indonesia tend to show the limitation of individuals' control upon their health. The policy of taking very much the privacy right of the victim into account has implicated the role of medical profession reducing the HIV transmission. This paper argues for increasing public accountability of medical practitioners and hospitals as public health agencies in protecting hidden transmission of HIV in society.